Abstract Filipe+Braumann+Roquete SPE 2008 - Filipe, Patrícia A.; Braumann, Carlos A.; Roquete, Carlos J. (My University, 2009)
Oral communication at the XVI Congresso Anual da Sociedade Portuguesa de Estatística (Vila Real, Oct. 1-4, 2008). Web page: http://home.utad.pt/~spe2008/ Study and statistical issues of multiphase animal growth models in random environments using stochastic differential equations.
Keywords: stochastic differential equations; animal growth; multiphase growth models; Random environments